Fatty acid bile acid conjugates (FABACs)—New molecules for the prevention of cholesterol crystallisation in bile. Issue 1 (1st January 2001) - Gilat, T; Somjen, G J; Mazur, Y; Leikin-Frenkel, A; Rosenberg, R; Halpern, Z; Konikoff, FM
Abstract : BACKGROUND: Cholesterol gall stones are a frequent disease for which at present surgery is the usual therapy. Despite the importance of bile acids it has become evident that phospholipids are the main cholesterol solubilisers in bile. Even phospholipid components, such as fatty acids, have anticrystallising activity. AIM: To synthesise fatty acid bile acid conjugates (FABACs) and study their effects on cholesterol crystallisation in bile in vitro and in vivo. METHODS: FABACs were prepared by conjugation of cholic acid at position 3 with saturated fatty acids of variable chain length using an amide bond. Cholesterol crystallisation and its kinetics (crystal observation time, crystal mass) were studied in model bile, pooled enriched human bile, and fresh human bile using FABACs with saturated fatty acids of varying chain length (C-6 to C-22). Absorption of FABACs into blood and bile was tested in hamsters. Prevention of biliary cholesterol crystallisation in vivo was tested in hamsters and inbred mice. RESULTS: FABACs strongly inhibited cholesterol crystallisation in model as well as native bile. The FABACs with longer acyl chains (C-16 to C-22) were more effective. At a concentration of 5 mM, FABACs almost completely inhibited cholesterol crystallisation in fresh human bile for 21 days. FABACs were absorbed and found in both portal and heart blood of hamsters. Levels in bile were 2–3 times higher than in blood, indicating active secretion. Appreciable levels were found in the systemic circulation 24–48 hours after a single administration. Ingested FABACs completely prevented the formation of cholesterol crystals in the gall bladders of hamsters and mice fed a lithogenic diet. CONCLUSIONS: FABACs are potent inhibitors of cholesterol crystallisation in bile. They are absorbed and secreted into bile and prevent the earliest step of cholesterol gall stone formation in animals. These compounds may be of potential use in cholesterol gall stone disease in humans.